Children’s engagement in self-learning modules (SLMs) amid the pandemic: A predictive analysis on the role of internet access, household food security, and parental involvement to modular classes - Collado, Zaldy C. (Animo Repository, 2021)
This study examines essential factors that affect children’ quality of response towards a non-traditional learning platform specifically, self- learning modules (SLMs) as Philippine public school’s mode of service- learning delivery. Our objective is to determine the predictive power of access to internet, household food security, and parental involvement on the level of students’ engagement in these modular classes amid the health crisis. Drawing online responses from parents of public-school students (n=359), our regression analysis confirms the viability of our model F(3,355) = 19.2, p